Palliative Care in Patients with Kidney Failure: Bibliometric Analysis - Dian Ratri; Erna Rochmawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Palliative care for patients with kidney failure is increasingly recognized as an important approach to improving quality of life through symptom control, psychosocial and spiritual support, and strengthening shared decision-making, yet the global knowledge landscape remains fragmented and incompletely mapped. Mapping publication performance, geographic distribution of country contributions, and the dynamics of research themes related to palliative care in kidney failure patients through bibliometric analysis. A bibliometric study was conducted using the Scopus database spanning the last 10 years. The search strategy combined the keywords palliative care and kidney failure. From 4,730 initial findings, a gradual narrowing was performed to obtain 2,397 documents meeting the criteria, consisting of 1,974 research articles and 423 review articles. Descriptive analysis was used for annual publication trends and country contributions, while VOSviewer version 1.6.18 was used to map keyword co-occurrence, overlay maps, and density maps. Keyword mapping places demographic and clinical terms as central nodes, with primary clusters reflecting acute conditions and severity indicators including acute kidney injury and respiratory infectious complications, chronic kidney disease and dialysis therapy clusters linked to themes of palliative care, terminal care, quality of life, psychology, and conservative care, and geriatric clusters and service outcomes such as hospitalization, comorbidities, risk factors, length of stay, and mortality. The overlay map demonstrates a shift in themes from patient support and quality of life to a stronger focus on clinical outcomes, comorbidities, and infectious and respiratory contexts in the more recent period, while the density map highlights the largest hotspots in the elderly population and the kidney disorder theme networked with hospitalization outcomes.Palliative care research in patients with kidney failure is dominated by clinical themes and service outcomes, while patient-centered themes such as quality of life, psychology, and terminal and conservative care emerge as important but relatively less prominent. Strengthening studies measuring meaningful outcomes for patients and caregivers, standardizing terminology and reporting, and multicenter collaboration across countries are needed to reduce contextual bias and enhance global relevance.